(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
Radio has played and is playing an important role in public awareness and mass communication. Marconi’s invention revolutionised the whole Western World in the last century but in India its impact was reflected very late. Earlier programmes on radio were themed on infotainment, i.e. a combination of information and entertainment. But in post-independence era a third factor of education too became an integral part of broadcast. An exhaustive cum descriptive study has been carried out to find out the impact of the programmes done by AIR on demonetisation of Rs.500 and Rs. 1000 currency notes. Impact of demonetisation on Indian society has been studied by co relating it’s with my earlier study, expanding from 2003 to 2016. The results are interesting and even support some pre established facts of wave’s communication. These days, it is becoming a common notion that Radio may not survive in long run and it may even become obsolete in near future. Feedbacks given by the listeners through various means have broken the notion of decreasing popularity of wave’s communication. But the impacts of some programmes like ’Mann Ki Baat’ of our Prime Minister Sh. Narender Modi and recently mounted series of programmes on Demonetisation further break this myth. During the gestation period of Demonetisation five programmes were done on National Hook up in the form of live Phone-in Programmes, four National programmes under National Programmes of Talks, eight programmes on FM Rainbow Networks and on an average one or two programmes were broadcast daily on local networks. Besides this Prime Minister Shri Narendera Modi raised the issues twice in his popular series, “Mann Ki Baat”. Radio series and programmes of mass appeal can undergo a long way by having deep and sustaining effect on target audience. By adopting different formats of programme production, monotony of the listeners can be broken. During the rising trend of new media the traditional wave media of Radio can prove as a source of Government and Public participation for continuous advancement of knowledge among the masses, particularly in remote and rural areas, where the new media is yet to gain its assess. This study shows that during any unforeseen situation that may arise can be faced by learning process,